The Effect of Gratitude and Self-Control on Fear of Missing Out Syndrome (FOMO): Outfit Trends for UIN Malang Students - Eny Halimiyah (Penerbit Hellow Pustaka, 2025)
Based on the results of the study, it can be concluded that UIN Maulana Malik Ibrahim Malang students have a moderate level of gratitude. This is indicated by data showing that there are 56.8% of respondents. For self-control, the average respondent has a moderate level of self-control, as evidenced by 78.4% of respondents. For the FoMo level, the average respondent has a moderate level. This is indicated by data showing that there are 67.6%. This study resulted in a very significant negative influence of self-control and gratitude on FoMO. In this study, when someone with low gratitude is influenced by the desire to get self-satisfaction and feels inadequate about the things received in their life. Self-control has the intent and purpose so that each individual can direct and also regulate individual behavior in everyday life where this self-control is very important for the personality of each individual so that it can help each individual in regulating and overcoming various things. This explanation is reinforced by previous research by Norma which states that if students have high self-control, the tendency for social media addiction in students is low and results in students having low FoMO because one of the factors of FoMo is frequent use of social media. Conversely, if students' self-control is low, the tendency for social media addiction will be high so that they have a high level of FoMO. This research is also reinforced by other research conducted by Aritonang which states that if there is a positive relationship, namely the higher the gratitude, the higher the self-assessment, thus reducing FoMO. This can happen because one of the indicators of FoMo is the low fulfillment of psychological needs for oneself.